Edge-nitrogenated graphene nanoplatelets as high-efficiency counter electrodes for dye-sensitized solar cells. Issue 18 (25th April 2016) - Wang, Guiqiang; Zhang, Juan; Hou, Shuo; Zhang, Wei; Zhao, Zengdian
Abstract : ENGNPs were prepared by a simple pin-grinding process at room temperature and demonstrated to be efficient counter electrodes for DSCs. Abstract : Edge-nitrogenated graphene nanoplatelets (ENGNPs) are prepared by a simple and eco-friendly mechanochemical pin-grinding process using flake graphite as the precursor in the presence of nitrogen and investigated as the counter electrodes of dye-sensitized solar cells (DSCs). SEM images and nitrogen adsorption analysis indicate an effective and spontaneous delamination of the pristine graphite into small graphene nanoplatelets by a mechanochemical pin-grinding process. The mechanochemical cracking of the graphitic C–C bond generates activated carbon sites that react directly with nitrogen at the broken edges. The resultant ENGNPs are deposited on a fluorine-doped tin oxide (FTO) substrate by spray coating, and their electrocatalytic activities are investigated systemically in the I − /I3 − redox electrolyte. Electrochemical measurements show that the ENGNP electrode possesses excellent electrocatalytic activity for the redox reaction of I − /I3 − as evidenced by the low charge-transfer resistance at the interface of the electrode and electrolyte. Under 100 mW cm −2 illumination, the DSC with the optimized ENGNP counter electrode achieves a conversion efficiency of 7.69%, which is comparable to that of the device with Pt counter electrode.